1971
DOI: 10.1126/science.174.4008.507
|View full text |Cite
|
Sign up to set email alerts
|

Polyadenylic Acid Sequences: Role in Conversion of Nuclear RNA into Messenger RNA

Abstract: Polyadenylic acid [poly(A)] segments containing 150 to 250 nucleotides appear to be covalently linked to heterogeneous nuclear RNA (HnRNA) and messenger RNA (mRNA) in eucaryotic cells. The poly(A) is synthesized in the nucleus, and is probably linked initially to HnRNA that is ultimately transported as mRNA to the cytoplasm. Studies with inhibitors of RNA or poly(A) synthesis indicate that synthesis of poly(A) segments is independent of transcription. The poly(A) marker may prove useful to elucidate mRNA modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
194
1
1

Year Published

1972
1972
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 566 publications
(205 citation statements)
references
References 23 publications
9
194
1
1
Order By: Relevance
“…Because cordycepin interferes with polyadenylation, it was concluded that the probe must have been hybridized in the untreated cells. However, cordycepin has not been used in previous studies on mammalian cell nuclear RNA metabolism for more than 1-3 h (Siev et al, 1969;Penman et al, 1970;Darnell et al, 1971;Mendecki et al, 1972) because of severe toxicity effects. Moreover, it has been clearly established that cordycepin inhibits the production of cytoplasmic mRNA in HeLa cells within 25-40 min (Penman et al, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Because cordycepin interferes with polyadenylation, it was concluded that the probe must have been hybridized in the untreated cells. However, cordycepin has not been used in previous studies on mammalian cell nuclear RNA metabolism for more than 1-3 h (Siev et al, 1969;Penman et al, 1970;Darnell et al, 1971;Mendecki et al, 1972) because of severe toxicity effects. Moreover, it has been clearly established that cordycepin inhibits the production of cytoplasmic mRNA in HeLa cells within 25-40 min (Penman et al, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…One of our early experiments that suggested a lag before the addition of some of the poly(A) segments involved the use of actinomycin (2,4,31). This drug stops the synthesis of hnRNA, but for a brief period allows presumably complete ImRNA molecules to acquire poly(A) within the nucleus.…”
Section: Effects Of Actinomycin On Poly(a) Synthesismentioning
confidence: 99%
“…2 shows the superimposed electrophoretic patterns of polyribosome-associated [3H]adenosine labeled RNA from free and membrane-bound ribosomes and of the respective RNAase digests. A peak with the electrophoretic mobility described for poly-A [1] was observed in both the RNAase digests of free and membrane-bound polyribosomal RNA. By contrast, no RNAase resistant material appeared in the digests of [3H]uridine labeled RNA analyzed in the same way.…”
Section: Resultsmentioning
confidence: 73%
“…see the review by Darnell et al [1]). Poly-A sequences have also been found in mRNA of both DNA viruses [2,3] and RNA viruses [4][5][6].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation